Evaluation of Epicardial Adipose Tissue in Patients of Type 2 Diabetes Mellitus by Echocardiography and its Correlation with Intimal Medial Thickness of Carotid Artery - Wang, Zihang; Zhang, Yuhong; Liu, Weiwei; Su, Benli (Experimental and Clinical Endocrinology & Diabetes, 2017)
The present study aimed to evaluate the diagnostic value of echocardiography in measuring the thickness of epicardial adipose tissue (EAT) of the patients of type 2 diabetes mellitus (T2DM) and its correlation with the intimal-medial thickness of the carotid artery (cIMT) to investigate the relationship between EAT and cIMT. 68 patients of T2DM were enrolled and were divided into 2 groups: group of T2DM with duration≤10 years (35 cases) and group of T2DM with duration>10 years (33 cases). And 30 healthy subjects were enrolled as the control group. The thickness of EAT and cIMT were measured by echocardiography and high-frequency ultrasonography. The thickness of EAT and IMT of the carotid artery of 2 type 2 diabetic groups (duration≤10 years and>10 years) were significantly higher than that of the control group (all p<0.05), and the thickness of EAT and cIMT of the group of T2DM with duration>10 years were significantly higher than that of the group of T2DM with duration≤10 years (p<0.05). In univariate analysis, the thickness of EAT was positively and significantly associated with age (r=0.412, p<0.05), BMI (r=0.566, p<0.05), waist circumference (r=0.475, p<0.05), LDL (r=0.425, p<0.05), TG (r=0.496, p<0.05), duration of diabetes (r=0.384, p<0.05) and cIMT (r=0.456, p<0.05). In multiple stepwise regression analyses, age, BMI and IMT of carotid artery were appeared to be significantly associated with EAT (p<0.05 for all). In conclusion, routine screening of EAT and cIMT by ultrasonography in type 2 diabetic patients helps us to predict cardiovascular risks and prevent further development of cardiovascular complications.
Keywords: epicardial adipose tissue; type 2 diabetes mellitus; intimal-medial thickness; carotid artery; echocardiography